Combined prognostic utility of ST-segment recovery and myocardial blush after primary percutaneous coronary intervention in acute myocardial infarction - Sorajja, Paul; Gersh, Bernard J; Costantini, Costantino; McLaughlin, Michael G; Zimetbaum, Peter; Cox, David A; Garcia, Eulogio; Tcheng, James E; Mehran, Roxana; Lansky, Alexandra J; Kandzari, David E; Grines, Cindy L; et al. (European heart journal, 2005)
ST-segment recovery (SigmaSTR) and myocardial blush (MB) evaluate different elements of microcirculatory integrity after reperfusion therapy in acute myocardial infarction (AMI). We sought to determine whether the combination of SigmaSTR and MB after primary percutaneous coronary intervention (PCI) in AMI has greater prognostic utility than either measure alone. The 30 days and 1 year clinical outcomes of 456 patients were assessed as a function of SigmaSTR and MB after primary PCI from the CADILLAC trial. SigmaSTR and MB were concordant (> or =70% SigmaSTR and MB grade 2/3 or <70% SigmaSTR and MB grade 0/1) in 60.1% of patients and discordant in 39.9% of patients. The greatest survival was observed among patients with complete SigmaSTR (> or =70%) and MB grade 2/3 in whom the cumulative rates of death at 30 days and 1 year were 0.6 and 1.2%, respectively. Poorest survival was observed among patients with incomplete SigmaSTR (<70%) and reduced MB (grade 0/1), in whom 30 days and 1 year rates of death were 8.3 and 10.1%, respectively. Intermediate outcomes were present in patients with discordant MB and SigmaSTR. By multivariable analysis, however, SigmaSTR was an independent correlate of survival at 30 days and 1 year (P=0.05 and 0.01, respectively), whereas MB was no longer predictive (P=0.38 and 0.72, respectively). SigmaSTR and MB are not infrequently discordant after primary PCI. By univariate analysis, both measures of reperfusion success strongly correlate with survival and assessment of both yields incremental prognostic information beyond either measure alone. By multivariable analysis, however, SigmaSTR is the stronger prognostic variable.